2015
DOI: 10.17569/tojqi.41736
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Management Problems and Coping Strategies of Turkish Student EFL Teachers

Abstract: Classroom management (CM) is one of the most cited problems of pre-service teachers. This study aims to have a closer look at the issue within a qualitative research design by eliciting problems, coping strategies, and the sources of those coping strategies related to CM during teaching practicum. The participants of the study were 12 student EFL teachers (eight female and four male) completing their teaching practicum at Anadolu University, Faculty of Education, English Language Teacher Training Program. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 19 publications
10
44
0
4
Order By: Relevance
“…So in-service relied on their relations with and knowledge of the students in the lesson while pre-service teachers relied more on their academic knowledge. This is in line with Merç & Subaşı's (2015) finding that pre-service teachers rely on their knowledge from methodology lessons.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…So in-service relied on their relations with and knowledge of the students in the lesson while pre-service teachers relied more on their academic knowledge. This is in line with Merç & Subaşı's (2015) finding that pre-service teachers rely on their knowledge from methodology lessons.…”
Section: Discussionsupporting
confidence: 90%
“…Using Scrievener's (2005) classification of classroom management, he found that the most problematic area was managing critical moments, especially in terms of maintaining the silence and controlling the noise level. Merç and Subaşı (2015) investigated the problems of student teachers about classroom management and how they cope with these problems. They found that problems generally come from students, the teaching point and materials, and cooperating teachers.…”
Section: Classroom Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of her study, talking to friends, making noise, dealing with other things and talking without permission were recorded as mostly faced misbehaviors. Another misbehavior which was commonly occurred that was making noise (singing and shouting) was also consistent with the result of study conducted by Merç & Subaşı (2015) where among those misbehavior problems, the level of noise in the classroom was placed as the first (33 %).…”
Section: Findings and Discussionsupporting
confidence: 86%
“…Teacher competency has much more to do with teachers' self-efficacy beliefs (Hoy, Hoy & Davis, 2009;Tschannen-Moran & Hoy, 2007). This is buttressed by other researchers (Kyriacou, 1991;Merç and Subaşı, 2015) that teachers with several years of teaching experience find it difficult to deal with emerging issues in classroom management.…”
Section: Discussionmentioning
confidence: 93%